1978
DOI: 10.1002/ijc.2910220204
|View full text |Cite
|
Sign up to set email alerts
|

Antibody patterns to herpesviruses in Kaposi's sarcoma. II. Serological association of american Kaposi's sarcoma with cytomegalovirus

Abstract: The prominent finding of this extended serologic analysis on American and African Kaposi's sarcoma (KS) patients and appropriately matched control groups is the detection of a specific serologic association of cytomegalovirus (CMV) with American KS patients. All American KS sera contained CMV antibodies and their geometric mean titers (GMT) were significantly higher than those in sera of melanoma patients (GMT ratio k = 5.3 to 7.7 by complement fixation [CF], k = 8.9 by indirect hemagglutination [IHA]) or in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0
1

Year Published

1980
1980
2007
2007

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 195 publications
(35 citation statements)
references
References 37 publications
0
34
0
1
Order By: Relevance
“…Admittedly, given the high general level of enthusiasm for IFN at that time, one did not need to invoke an elaborate rationale to justify studying IFN in any sort of cancer. Nonetheless, we believed that an agent with antiproliferative, immunomodulatory and antiviral activities might be a particularly appropriate candidate for evaluation in a neoplasm that was associated with immunodeficiency and in which cytomegalovirus had been implicated as a potential etiologic factor (wrong herpesvirus, right idea) [8,9]. In subsequent clinical trials in larger numbers of patients we confirmed that high-dose IFNα was active against KS, whereas the administration of lower, better tolerated IFN doses rarely induced KS regression [10].…”
Section: Ifnα As Single Agent Therapy -A Requirement For High Ifn Dosesmentioning
confidence: 60%
“…Admittedly, given the high general level of enthusiasm for IFN at that time, one did not need to invoke an elaborate rationale to justify studying IFN in any sort of cancer. Nonetheless, we believed that an agent with antiproliferative, immunomodulatory and antiviral activities might be a particularly appropriate candidate for evaluation in a neoplasm that was associated with immunodeficiency and in which cytomegalovirus had been implicated as a potential etiologic factor (wrong herpesvirus, right idea) [8,9]. In subsequent clinical trials in larger numbers of patients we confirmed that high-dose IFNα was active against KS, whereas the administration of lower, better tolerated IFN doses rarely induced KS regression [10].…”
Section: Ifnα As Single Agent Therapy -A Requirement For High Ifn Dosesmentioning
confidence: 60%
“…Originally described as 'idiopathic multiple pigmented sarcoma' of the skin by the Hungarian dermatologist Moritz Kaposi in 1872 [2], KS was noted to be more frequent in East and Central Africa in the 1920s, and its uneven geographical distribution in Africa was catalogued more carefully in the early 1960s [3]. This led to the hypothesis that KS might be caused by a virus and in 1972, Giraldo et al [4] identified herpesvirus-like particles in short-term cultures of KS biopsies which were thought to be cytomegalovirus (CMV) [5]. Subsequent attempts to identify CMV DNA in such samples by DNA hybridization were unsuccessful and involvement of a herpesvirus was assumed to be unlikely [6].…”
Section: History and Involvement In Diseasementioning
confidence: 99%
“…33 These events have been demonstrated in experimental systems by infecting cells in vitro at high virus multiphicity. @7 It has also been shown that defective herpesviruses (types I and II), as well as CMV, may main tain their transforming ability.4'-48-50 It is likely that under these circumstances, these viruses, even though they are defec tive, retain oncogenic potential in individ uals with certain genetic and immunologic backgrounds.…”
Section: Ca-acancer Journal Forcliniciansmentioning
confidence: 99%